Flora and vegetation on cryoturbated and associates habitats around abra Apacheta, Ayacucho - Huancavelica (Peru) - Cano, Asunción (2011)
around Abra Apacheta, in Cangallo (Ayacucho) and Huaytara (Huancavelica) Provinces. The aims of this study were: to study vascular floristic composition of High Andes (over 4500 m of altitude) and characterize highland vegetation. There were used conventional techniques for botanical collection and vegetation coverage measurements by intersection-line transects and Point Quadrat modifyed method. There were registered 134 species of vascular plants (Pteridophytes, Gymnospems, Eudicots and Monocots) grouped in 60 genera and 23 families. Eudicots were the dominant group with 74% of the total registered, 82% in genera and 77% in species; followed by Monocots with 13%, 13% and 21% in the previous categories. Monilophytes (ferns) were poorly represented by two families (9%), two genera (3%) and two species (1%); while Gymnosperms only registered one specie (Ephedra rupestris Benth.). By the quantitative analysis three types of plant communities associated to cryoturbated soils were characterized, we also report two types of associated vegetation: grasslands and rocky areas.